Evaluación de las funciones cognitivas y la calidad de vida de un adulto mayor de 80 años de edad del Centro Gerontológico de la ciudad de Quevedo - Guanoquiza Calapaqui, Brayan Michael (2023)
One of the most significant changes that human beings have is the transition from adulthood to old adulthood. For many, this change is a setback in the person's functionality, because one of the most important characteristics of this period is the loss of independence, finally, the research topic of evaluation of the cognitive functions and quality of life of an adult over 80 years of age from Quevedo is raised, in which it is intended to comply with the general objective of evaluating the cognitive functions of an adult over 80 years of age in a gerontological center in the city of Quevedo, in order to develop a treatment plan that contributes to the quality of life of the older adult, for this it is necessary to establish specific objectives; First, investigate the different bibliographic sources on the cognitive functions and quality of life of the elderly. Second, apply psychological evaluation instruments to determine the state of cognitive functions and quality of life of an older adult. Third, present a treatment plan that allows the stimulation of cognitive functions and contributes to the quality of life of the older adult. Governed by the clinical and forensic research line, and the forensic clinical evaluation research subline.